Relation of Secondhand Smoking to Mild Cognitive Impairment in Older Inpatients - Giuseppe Orsitto; Vincenzo Turi; Amedeo Venezia; Francesco Fulvio; Cosimo Manca (The Scientific World Journal, 2012)
Up to now, controversy still exists regarding the role of secondhand smoking (SHS) in developing cognitive impairment. This study aimed to evaluate the prevalence of SHS in hospitalized older patients with cognitive deficit, particularly in those with mild cognitive impairment (MCI). Smoking history was classified into four groups: never smokers, former-active smokers/no SHS, active smokers, and secondhand smokers, and cognitive function into three levels: normal cognition (C), MCI, and dementia. A total of 933 older subjects with diagnoses of MCI (n=98), dementia (n=124), or C (n=711) were enrolled in this cross-sectional study. As expected, patients with dementia had significantly higher frequency of former-active smokers than cognitively normal. Moreover, patients with MCI showed a significantly higher frequency of active and secondhand smokers than patients with dementia or C. A smoking history is very frequent in older patients with dementia. Patients with MCI had even higher rate of exposure to active or secondhand smoking.